ANALISIS DAN PERANCANGAN SISTEM INFORMASI DALAM PEMBAYARAN ADMINISTRASI KEUANGAN SISWA DI SMA NOMMENSEN JAMBI - Lamtiur, Hosianna; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Nommensen High School is one of the Educational Institutions in Jambi City having its address at Jalan Barau - Barau I Kel. Pakuan Baru Kec. South Jambi which was founded in 1988, which has a number of 195 students with increasing numbers during the Nommensen High School in Jambi City experienced a development. This development requires the existence of a means to accelerate performance and efficiency in School Administration especially School Financial Administration such as new student registration payment of tuition fees and committee fees, school financial expenditures and so on therefore there is a need for a school financial administration management information system that can record, process and produce a fast school financial information system. In this system research system design is used using UML mo deling which produces use case diagrams, activity diagrams and class diagrams. The results of this study were in the form of a prototype. The purpose of this study is expected to facilitate the management of school financial administration to be faster, more precise and accurate.